Technical Considerations and Protocol Optimization for Neonatal Salivary Biomarker Discovery and Analysis - Yen, Elizabeth; Kaneko-Tarui, Tomoko; Maron, Jill L. (Frontiers in Pediatrics, 2021)
Non-invasive techniques to monitor and diagnose neonates, particularly those born prematurely, are a long-sought out goal of Newborn Medicine. In recent years, technical advances, combined with increased assay sensitivity, have permitted the high-throughput analysis of multiple biomarkers simultaneously from a single sample source. Multiplexed transcriptomic and proteomic platforms, along with more comprehensive assays such as RNASeq, allow for interrogation of ongoing physiology and pathology in unprecedented ways. In the fragile neonatal population, saliva is an ideal biofluid to assess clinical status serially and offers many advantages over more invasively obtained blood samples. Importantly, saliva samples are amenable to analysis on emerging proteomic and transcriptomic platforms, even at quantitatively limited volumes. However, biomarker targets are often degraded in human saliva, and as a mixed source biofluid containing both human and microbial targets, saliva presents unique challenges for the investigator. Here, we provide insight into technical considerations and protocol optimizations developed in our laboratory to quantify and discover neonatal salivary biomarkers with improved reproducibility and reliability. We will detail insights learned from years of experimentation on neonatal saliva within our laboratory ranging from salivary collection techniques to processing to downstream analyses, highlighting the need for consistency in approach and a global understanding of both the potential benefits and limitations of neonatal salivary biomarker analyses. Importantly, we will highlight the need for robust and stringent research in this population to provide the field with standardized approaches and workflows to impact neonatal care successfully.